Professional Development of Novice Special Education Teachers - Silmara de Oliveira Gomes Papi (Universidade Federal do Rio Grande do Sul, 2018)
The professional development of novice teachers in the profession and in special education is poorly understood, despite its relevance to the improvement of teaching. This study analyzes the challenges faced by such teachers with a view to understanding their professional development. The participants in the research were teachers of classrooms equipped with multifunctional resources (SRM) in state schools. The research follows a critical-dialectic approach and a qualitative focus. The results indicate deficiencies in the professional development of novices, who experience difficulties related to teaching and bureaucracy, despite having specific training in the area. They also feel alienated in the schools and seek alternatives to fill existing gaps related to their professional practice.